2021
DOI: 10.3390/pr9010158
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Heavy Residual Oil by Pulsed Nuclear Magnetic Resonance

Abstract: A study on the catalytic oxidation of heavy residual oil (HRO) was carried out. The thermodynamic parameters of components of HRO oxidation products were studied by pulsed nuclear magnetic resonance (NMR). A method for the quantitative assessment of thermodynamic parameters of HRO components and oxidized bitumen using pulsed NMR is presented. The relationship between NMR parameters and the viscosity of HRO and its oxidation products is established. The obtained results prove the possibility of using pulsed NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Initially, a study on the catalytic oxidation of heavy residual oil was carried out by A.V. Vakhin et al [10]. The thermodynamic parameters of heavy residual oil oxidation products were studied using pulsed nuclear magnetic resonance, and the relationship between nuclear magnetic resonance parameters, the viscosity of heavy residual oil and its oxidation products was established.…”
Section: Diffusion and Kinetic Modeling In Fossil-fuel-based Feedstocksmentioning
confidence: 99%
“…Initially, a study on the catalytic oxidation of heavy residual oil was carried out by A.V. Vakhin et al [10]. The thermodynamic parameters of heavy residual oil oxidation products were studied using pulsed nuclear magnetic resonance, and the relationship between nuclear magnetic resonance parameters, the viscosity of heavy residual oil and its oxidation products was established.…”
Section: Diffusion and Kinetic Modeling In Fossil-fuel-based Feedstocksmentioning
confidence: 99%
“…When the temperature was above 180 °C, the cracking reaction rate increased; however, the coke generation rate also increased. Vakhin et al [ 9 ] found that the asphaltene content of heavy oil residue from the Elkhovsky oil refinery increased after catalytic oxidation at 250 °C by air with manganese dioxide (80 wt.%), iron dioxide, and silicon oxide. Nassar et al [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ] adsorbed asphaltenes on nano-catalysts (e.g., CaO, Co 3 O 4 , Fe 3 O 4 , MaO, NiO, and PdO), and then their catalytic oxidation effect was investigated by thermogravimetric analysis at temperatures above 200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate deposits containing organic matter in Russia are found on the East European platform and the Urals, on the northeastern slope of South Timan, in the Perm region, Udmurtia, Tatarstan, and Bashkiria, and are confined to the Semiluki horizon of the Lower Frasniansubstage [30][31][32][33]. Their analogs are also found in the Sargaevskiy, Processes 2021, 9, 1893 2 of 11 Buregskiy, and Askynskiy horizons of the Frasnian Stage, and partially in the Famennian Stage in the territory of the Kama-Kinelskpaleotrough.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many companies, institutes, and research groups in different countries are engaged in the creation of innovative technologies for the extraction and processing of hydrocarbons from carbonate rocks [31,34,35,[51][52][53][54][55][56][57][58]. Thus, the present work is devoted to study the composition of the extracted hydrocarbons (petroleum hydrocarbons) from Semiluksko-Mendymsky horizon carbonate rock containing organic matter under hydrothermal conditions at different temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%